Association of the T102C (rs6313) polymorphism of the HTR2A serotonin receptor gene with the development of depressive disorders in children with somatoform vegetative dysfunction of the respiratory system - Невоя, Марія; Pypa, Лариса; Svistilnik, Руслан (Psychosomatic Medicine and General Practice, 2023)
This text is the thesis of the VI scientific and practical conference with international participation "PSYCHOSOMATIC MEDICINE: SCIENCE AND PRACTICE", which will be held on November 2-3, 2023 in the format of online broadcasting. The following is devoted to the study of the relationship between the T102C (rs6313) serotonin receptor gene HTR2A polymorphism and the risk of developing somatoform vegetative dysfunctions of the respiratory system.